Analisis Capaian Perkembangan Sosial Anak Usia 11 Bulan Berdasarkan Standar Tingkat Pencapaian Perkembangan Anak - Eka Damayanti; Umaemah Marsuki AR; Ismawati Ismawati (JECED : Journal of Early Childhood Education and Development, 2020)
This study aims to determine the criteria for social development in children 11 months based on the Standard Level of Child Development Achievement and formulate appropriate stimulation based on the theory of child development. The research was conducted using a descriptive qualitative approach. The research subjects were two children aged 11 months who were selected by purposive sampling. The data were collected from observation and direct interview techniques then analyzed descriptively. The results showed that both children (HM and D) had met the age standard in terms of research desires with various body movements and simple word expressions, how to express feelings such as, how to apply and kiss. The forms of stimulation performed by parents or caregivers of children include: (1) building attachment with children; (2) invite the child to have a conversation or A with the closest person; and (3) inviting children to play with their peers.